Analysis of integrity tests for checking integrity constraints in a distributed database - Alwan, Ali Amer; Ibrahim, Hamidah; Udzir, Nur Izura (2007)
An important aim of a database system is to guarantee database consistency, which means that the data contained in a database is both accurate and valid. Integrity constraints represent knowledge about data with which a database must be consistent. The process of checking constraints to ensure that update operations or transactions, which alter the database, will preserve its consistency has proved to be extremely difficult to implement, particularly in a distributed database. Checking the consistency of a database state will generally involve the execution of integrity tests on the database which verify whether the database is satisfying its constraints or not. This paper presents the various types of integrity tests as discussed in the literature and analyses the performance of the constraint checking with respect to the amount of data transferred across the network and the number of sites involved when different type of test is selected. This analysis is important for selecting the suitable test during the process of checking integrity constraints in a distributed database so that the process of checking can be performed at the local site (involves a single site) to reduce the amount of data transferred across the network which is known to be the most critical factor that influences the performance of a checking mechanism.